Change forces with a vengeance - Fullan, Michael (London ; New York : RoutledgeFalmer, 2003)
Michael Fullan is arguably one of the world's leading authors on the issue of educational change. In this eagerly awaited trilogy Fullan explores why school reform is not as easy as first expected.
Book Cover; Title; Contents; List of Figures; Preface; New Horizons; Moral Purpose Writ Large; New Lessons for Complex Change; Tri-Level Reform: The School; Tri-Level Reform: The Role of the District; Tri-Level Reform: The State; Leadership and Sustainability; References; Index.
Includes bibliographical references (pages 107-110) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Educational change; Educational planning; School improvement programs; Enseignement -- Réforme.; EDUCATION -- Administration -- General; School improvement programs; Educational change; Educational planning